2014
DOI: 10.17113/ftb.52.04.14.3622
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin-Protected PC12 Cells Against Glutamate-Induced Oxidative Toxicity

Abstract: SummaryGlutamate is a major excitatory neurotransmi er present in the central nervous system. The glutamate/cystine antiporter system x c -connects the antioxidant defense with neurotransmission and behaviour. Overactivation of ionotropic glutamate receptors induces neuronal death, a pathway called excitotoxicity. Glutamate-induced oxidative stress is a major contributor to neurodegenerative diseases including cerebral ischemia, Alzheimer's and Huntington's disease. Curcuma has a wide spectrum of biological ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 57 publications
2
17
0
Order By: Relevance
“…We also used flow cytometric assay to show that gefitinib co‐treated with CUR, DMC, or BDMC reduced MMP and increased caspase‐ 3 activities in SAS cells. It is well known that some of anticancer drugs induced cell apoptosis through mitochondria‐dependent pathways and caspase‐dependent and ‐independent pathways . Based on these observations, we suggest that gefitinib combined with CUR, DMC, or BDMC for inducing cell apoptosis of SAS cells through mitochondria‐ and caspase‐dependent pathway.…”
Section: Discussionmentioning
confidence: 52%
“…We also used flow cytometric assay to show that gefitinib co‐treated with CUR, DMC, or BDMC reduced MMP and increased caspase‐ 3 activities in SAS cells. It is well known that some of anticancer drugs induced cell apoptosis through mitochondria‐dependent pathways and caspase‐dependent and ‐independent pathways . Based on these observations, we suggest that gefitinib combined with CUR, DMC, or BDMC for inducing cell apoptosis of SAS cells through mitochondria‐ and caspase‐dependent pathway.…”
Section: Discussionmentioning
confidence: 52%
“…The cell viability test with MTT assay was carried out as previous reported [14]. The doses of Glu and Hcy were applied as indicated.…”
Section: Mtt Assay Cell Viability Testmentioning
confidence: 99%
“…Hcy acts as an agonist at the glutamate binding site of the N-methyl-D-aspartate receptor [11]. The PC12 cell line, originally isolated from a pheochromocytoma in the rat adrenal medulla, has become an in vitro model for studying numerous problems in neurobiology, neurochemistry [12,13], and Alzheimer's and Parkinson's diseases [14]. Like glutamate, Hcy induced calcium influx, depolarization of mitochondrial membrane potential, and changes of Bcl-2 and Bcl-xL in the PC12 cell model [15].…”
mentioning
confidence: 99%
“…In our study, rats in the formaldehyde group had increased renal NO, while a lower NO level was found in formaldehyde+curcumin group, as compared to formaldehyde alone. Many studies showed that curcumin was able to decrease the NO synthase production in activated macrophages (37) and prevented the production of NO (38,39). Curcumin prevents the formation of peroxynitrite by its radical scavenging activity and also suppresses the NO synthesis through the inhibition of iNOS activity.…”
Section: Discussionmentioning
confidence: 99%